Mentorship, Leadership, and Research Their Place within the Social Science Curriculum - Snowden, Michael; Halsall, Jamie P. (International Perspectives on Social Policy, Administration, and Practice,, 2019)
This insightful volume details the implementation and challenges of the Teaching Excellence Framework (TEF), developed in the UK to ensure equal access to higher education for all social classes. It posits that a modern higher education institution requires a robust set of mechanisms - specifically mentorship, leadership, and research - to create high-quality teaching and learning. Noted contributors pose and answer key questions about the TEF in such areas as solution-focused teaching, mentoring for the job market, and social science curriculum development, using best practice examples in the field. These ideas and strategies carry great potential to improve the caliber of teaching and learning in universities, and with it, students' social mobility. Among the topics covered: Why have mentoring in universities? Reflections and justifications. Working with students as partners: developing peer mentoring to enhance the undergraduate student experience. The employers' reach: mentoring undergraduate students to enhance employability. Learn it and pass it on: strategies for educational succession. Mentoring mentees to mentor. Interdisciplinarity in higher education: the challenges of adaptability. Mentorship, Leadership, and Research will play a pivotal role in UK higher education since currently there is scant academic literature on practical tools to help universities to succeed at the TEF. A resource with international implications, it should interest sociologists of education and professionals in business strategy and leadership, social work, and community development. Michael Snowden is a Senior Lecturer in Mentoring Studies at the University of Huddersfield, UK. Jamie P. Halsall is a Reader in Social Sciences at the University of Huddersfield, UK. "Given the recent introduction of the Teaching Excellence Framework (TEF) in the United Kingdom, this timely book outlines effective practices to help earn the "Gold" standard. While considering TEF within the current climate of academic competition and critical evaluation, a diverse group of experts lay out why mentoring is one highly effective answer to the TEF standards and without compromising productivity in other service and research agendas. This book is a must read for academics and higher learning administrators alike." Leda Nath, Professor of Sociology, University of Wisconsin.